ASI Eksklusif Meningkatkan Perkembangan Pada Balita - SUGIHARTI, ROSI KURNIA (NHM PRESS, 2023)
The growth and development of children physically, mentally, socially, emotionally is influenced by nutrition, health and education. Since the baby is born until the age of one year will experience growth and development. This process takes place rapidly and is highly influenced by the environment however, it lasts very short and cannot be repeated again so it is referred to as the